2022
DOI: 10.1007/s40264-022-01164-5
|View full text |Cite
|
Sign up to set email alerts
|

Industry Perspective on Artificial Intelligence/Machine Learning in Pharmacovigilance

Abstract: TransCelerate reports on the results of 2019, 2020, and 2021 member company (MC) surveys on the use of intelligent automation in pharmacovigilance processes. MCs increased the number and extent of implementation of intelligent automation solutions throughout Individual Case Safety Report (ICSR) processing, especially with rule-based automations such as robotic process automation, lookups, and workflows, moving from planning to piloting to implementation over the 3 survey years. Companies remain highly interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…Even before the pandemic, automation and its potential benefits for PV activities were well recognized (Kassekert et al, 2022). Rules based automation, also known as robotic process automation (RPA), are well established and have been routinely used for several years by companies to assist in the processing of individual case safety reports [ICSRs; see (Kassekert et al, 2020) for an example].…”
Section: Introductionmentioning
confidence: 99%
“…Even before the pandemic, automation and its potential benefits for PV activities were well recognized (Kassekert et al, 2022). Rules based automation, also known as robotic process automation (RPA), are well established and have been routinely used for several years by companies to assist in the processing of individual case safety reports [ICSRs; see (Kassekert et al, 2020) for an example].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence technologies used in pharmacovigilance systems [3,6,8] Технология Technology [10]. Таким образом, помимо качественной обработки сообщений о нежелательных реакциях, поступающих от участников системы фармаконадзора, использование прогрессивных технологий позволяет осуществлять обзор источников литературы, мониторинг информации социальных сетей и оказать поддержку специалистам в процессах принятия решений [11,12]. Наиболее эффективно применение представленных технологий автоматизации в комплексе: интеллектуальная автоматизация должна дополняться автоматизацией на основе правил для облегчения рабочих процессов и элементами машинного обучения, оптимизированными для определенных наборов данных или задач [12].…”
Section: уровни автоматизации рабочих процессов в электронной системе...unclassified
“…Таким образом, помимо качественной обработки сообщений о нежелательных реакциях, поступающих от участников системы фармаконадзора, использование прогрессивных технологий позволяет осуществлять обзор источников литературы, мониторинг информации социальных сетей и оказать поддержку специалистам в процессах принятия решений [11,12]. Наиболее эффективно применение представленных технологий автоматизации в комплексе: интеллектуальная автоматизация должна дополняться автоматизацией на основе правил для облегчения рабочих процессов и элементами машинного обучения, оптимизированными для определенных наборов данных или задач [12]. Кроме того, по мнению исследователей, сокращение объема рутинной работы специа-листов по фармаконадзору при использовании AI позволит повысить ценность их деятельности, поскольку их квалификация, опыт и время будут использоваться в основном для экспертной оценки полученных результатов [11].…”
Section: уровни автоматизации рабочих процессов в электронной системе...unclassified
“…A recent industry survey on the use of AI and machine learning in pharmacovigilance indicated that pharmacovigilance organizations intend to move rapidly with the planning, piloting, and production implementation of intelligent automation, while also pointing out that regulatory guidance is a potential challenge 8 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] A recent industry survey on the use of AI and machine learning in pharmacovigilance indicated that pharmacovigilance organizations intend to move rapidly with the planning, piloting, and production implementation of intelligent automation, while also pointing out that regulatory guidance is a potential challenge. 8 Medicines Regulators also need innovation that can deliver for public health. The recent coronavirus SARS-CoV-2 vaccination campaign is a good example of this potential application of artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%